A new approach to probabilistic earthquake-induced tsunami risk assessment. (January 2016) - Jaimes, Miguel A.; Reinoso, Eduardo; Ordaz, Mario; Huerta, Benjamín; Silva, Rodolfo; Mendoza, Edgar; Rodríguez, Juan C.
Abstract: A new approach is proposed for the probabilistic financial risk assessment of earthquake-induced tsunami. The risk is evaluated in a probabilistic framework for a full set of hazard events including all uncertainties. The hazard is defined as a stochastic and historic set of events, collectively exhaustive and mutually exclusive, that describes the spatial distribution, the annual frequency and the randomness of the hazard intensity. The risk is expressed as losses in different terms: the average annual loss and the loss exceedance curve. These metrics are of particular importance for risk financing schemes and risk transfer instruments. As an illustrative example, this approach is applied to the probabilistic tsunami risk assessment for public schools in southern Mexico. Graphical abstract: Highlights: This work provides an approach to probabilistic earthquake-induced tsunami risk assessment. We outline the key steps that led to the financial risk assessment of earthquake-induced tsunami. This work serves to undertake a comprehensive tsunami risk assessment to structures. This work serves as a model for other coastal communities vulnerable to tsunamis.